PENDIDIKAN ISLAM DALAM PEMIKIRAN SYEIKH AHMAD SURKATI - Febrina, Widya (Jurnal Tawadhu, 2024)
Islamic education is one aspect of Islam as a whole. Therefore, the aim of Islamic education cannot be separated from the aim of human life in Islam, namely the aim of producing individual servants of Allah who are always devoted to Allah and are able to achieve a happy life in this world and in the afterlife. Even though Sheikh Ahmad Surkati is an important figure in the renewal of Islamic thought in Indonesia, especially in the field of education, his name is still rarely mentioned in the historical discourse on the struggle for Islamic thought in Indonesia. The aim of this research is to understand in depth the concept of Islamic education initiated by Sheikh Ahmad Surqati. His ideas had a great influence on Islamic education in Indonesia. The research method used in this research is the character study method. Sheikh Ahmad Surkati is a reformer in the world of Islamic education. This is proven by the generalization of educational intuition carried out by Sheikh Ahmad Surkati which has never existed before in Indonesia. Sheikh Ahmad Surqati was also a pioneer in the formation of an institutional system in the world of education. This is progress in the world of education. Sheikh Ahmad Surkati's contribution to the development and improvement of the developing education system in Indonesia is enormous.